The association between central ambulatory blood pressure and end-organ damage. (14th October 2021) - Lu, I N; Yu, S K; Smith, J; Woodcock-Smith, J; Jalaludeen, N; Cheriyan, J; Wilkinson, I; McEniery, C
Abstract: Background/Introduction: Central blood pressure (BP) measured in the clinic relates more strongly to end-organ damage and may be superior to brachial BP in predicting cardiovascular events. Measurement of central ambulatory BP (ABP) is now possible and emerging data suggest that central ABP is better correlated with left ventricular mass index (LVMI) than brachial ABP.1, 2 However, the association between central ABP and other measures of end-organ damage remains unclear. Purpose: We investigated the association between brachial or central ABP and end-organ damage, in a large community-based population of untreated individuals. Method: 1091 participants (mean age 45±18 years; 589 females) had simultaneous measurements of brachial and central ABP over 24 hours, using the Mobil-O-Graph device. Central ABP was derived using two waveform calibration methods (1: mean/diastolic BP; 2: systolic/diastolic BP). Participants also underwent measurement of aortic pulse wave velocity (aPWV; SphygmoCor device) in the clinic. In a subset of 675 individuals, LVMI was assessed by echocardiography and in 610 individuals, carotid intima-media thickness (CIMT) was measured, using ultrasound. 24-hour and daytime brachial and central ambulatory systolic BP (ASBP) and pulse pressure (APP) were considered. Results: The Pearson's coefficient for each correlation is listed in Table 1. LVMI was most strongly correlated with 24-hour central ASBP, using calibration method 1 (MAP/DBP; r=0.403, P<0.001). CIMT was most strongly correlated with daytime central ASBP, again derived from calibration method 1 (r=0.341, p<0.001), whereas aPWV measured in the clinic, was most strongly correlated with 24-hour central ASBP, derived from calibration method 2 (SBP/DBP; r=0.441, P<0.001). Based on z statistics, all correlations reported above were significantly stronger than equivalent correlations using brachial ASBP (P<0.001 for all three comparisons of correlation coefficients). Conclusion: Measurement of central ABP relates more closely to end-organ damage than equivalent measures based on brachial ABP. Central ABP may provide valuable additional information concerning cardiovascular risk above and beyond brachial ABP. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): British Heart Foundation